The method for high order modes parameters estimation in periodical structures - Paramonov, V.V.; Denisenko, D.V. (Вопросы атомной науки и техники, 2012)
The High Order Modes (HOM) parameters are calculated in traveling wave mode at one structure period for the reference set of the phase advance values, with real 3D geometry in the wide frequency range. For the structure with arbitrary length HOM parameters are interpolated basing on periodicity properties. The method resolution doesn’t depends on the number of periods in the structure and allows reliably identify interesting and important HOM parameters for long structures and in high frequency region. ВЧ-характеристики высших мод колебаний (ВМК) рассчитаны в режиме бегущей волны в широком диапазоне частот на одном периоде структуры в трехмерном приближении для опорного набора набегов фазы поля на период. Для структуры с произвольным числом периодов ВМК параметры интерполируются исходя из свойств периодичности. Разрешение метода не зависит от числа периодов в структуре и позволяет выявить важные особенности ВМК в длинных структурах и диапазоне высоких частот. ВЧ-характеристики вищих мод коливань (ВМК) розраховані в режимі бігучої хвилі в широкому діапазоні частот на одному періоді структури в тривимірному наближенні для опорного набору набігів фази поля на період. Для структури з довільним числом періодів ВМК параметри інтерполіруються виходячи з властивостей періодичності. Дозвіл методу не залежить від числа періодів в структурі і дозволяє виявити важливі особливості ВМК у довгих структурах і діапазоні високих частот.